A STUDY OF INTERNALISED STIGMA OF MENTAL ILLNESS IN BENUE STATE, NIGERIA - Mpem, Terungwa; Mase, Judith Ayangeawam (African Journal of Social and Behavioural Sciences, 2024)
Internalised stigma (IS) has consistently been considered as one of the major problems in the mentally ill populations. There are previous research attempts to examine its causes and proffer solutions. However, rates of internalized stigma of mental illness seem to have remained consistently high in Nigeria, especially in Benue State. This study examined the prevalence of internalized stigma among people with mental illness in Benue State. Data were collected in six selected local government areas in the State, Benue State University Teaching Hospital, Federal Medical Centre, Makurdi and six traditional psychiatric hospitals. A combination of multi-stage, simple random and purposive sampling methods, were used to select respondents for the study. A survey questionnaire was administered to 468 people living with mental illness and In-depth Interviews were held with people living with mental illness. Data collected were analysed using SPSS version 23. The findings revealed that 67.9% of the people suffering from mental illness had elevated internalized stigma. People living with mental illness who received traditional health care had elevated stigma scores more than those who attended orthodox hospitals (t = 4.404, df = 466, sig. 2-tailed (p) = 000). It was also revealed through in-depth interviews with people having mental illness that they took overdose of the drugs from the hospitals to forget about the public stigma they experienced. The paper recommended that government and non-governmental organizations should embark on public awareness to educate members of the public about mental illness, in order to reduce stigmatization against people living with mental illness.